Bis(1-benzoyl-7-methoxynaphthalen-2-yl) terephthalate - Sakamoto, Rei (International Union of Crystallography, 2013)
The title molecule, C(44)H(30)O(8), lies about a crystallographic inversion centre located at the centre of the central benzene ring. The benzene rings in the benzoyl and the terephthalate units make dihedral angles of 67.05 (7)° and 57.57 (7)°, respectively, with the naphthalene ring system. There is an intramolecular C—H⋯O interaction between the ketonic carbonyl O atom and an H atom on the naphthalene ring system. In the crystal, C—H⋯O interaction of the benzene ring in the benzoyl group and weak C=O⋯π interaction [O⋯centroid = 3.375 (2) Å] of the naphthalene ring with the O atom in the ketonic carbonyl group are observed. These interactions form layers parallel to the bc plane.